Analysis of importance priority to be studied on igniter system of 450 caliber X rocket - A. Zaldiansyah; N. Widianto; Y. H. Yogaswara; Y. Ruyat (Defense and Security Studies, 2022)
A rocket is a flying platform that gets energy from the combustion process that performs a thrust that is large enough to reach hypersonic speed. It becomes quite vital considering the speed of the combustion process in double configuration propellant type, which is r=7 mm/s. The ignition of the propellant is supported by a squib as a conductor of electricity to the igniter which will then conduct heat to the propellant in the rocket motor. The main focus of this research is to analyze the development potential of the X rocket igniter system. This research uses a Quantitative Method approach, with the research analysis using a Quality Function Deployment (QFD) approach. Based on the benchmark values ​​obtained from each supporting instrument used in the 450 caliber X rocket igniter system, the results were obtained on a priority scale for the development of a rocket igniter system as an effort to overcome the igniter from malfunctions when the operating system is running. The results show that the instruments that need to be developed are the squib, pyrotechnics, emergency button, ground system, and wiring system.